The effect of hormone replacement therapy on cognition and mood. (13th December 2022) - Sharma, Aditi; Davies, Rhianna; Kapoor, Aditi; Islam, Heraa; Webber, Lisa; Jayasena, Channa N.
Abstract: Objectives: To summarise the available data regarding the effect of hormone replacement therapy (HRT) on cognition and mood in women. Background: Complaints of impaired cognition and mood are common in the peri‐menopausal and menopausal period. There is debate as to whether HRT can ameliorate this phenomenon. Design: A literature search of studies using electronic databases was conducted. Both randomised control trials and observational studies were included. Patients: Perimenopausal and menopausal women. Results: Due to the heterogenicity of results it is challenging to draw firm conclusions. The preparations used in many of the studies are older regimes no longer routinely used clinically. The notion of a 'critical window' for HRT is compelling, suggesting HRT has a positive impact on cognition when administered in the peri‐menopausal or early postmenopausal period but may have negative effects on cognition in the older, postmenopausal woman. The evidence would seem to suggest importance of hormonal replacement in woman undergoing a surgical menopause, especially when young. It remains unclear for how long they ought to continue HRT though until at least the natural age of the menopause seems reasonable. Evidence for a positive effect of HRT on mood is more convincing, though possibly more efficacious in the younger age group. The effect of HRT on anxiety is less clear. Conclusions: Further study, particularly focusing on the more contemporaneous HRT preparations, is warranted before evidence‐based conclusions can be drawn.